#### Answer

$f(g(2))=2$
$g(f(-2)=-2$

#### Work Step by Step

We know that $g(2)=-2$ and $f(2)=f(-2)$ (because f is even):
$f(g(2)=f(-2))=f(2)=2$
$g(f(-2)=g(f(2))=g(2)=-2$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$f(g(2))=2$
$g(f(-2)=-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.